Gone with the crisis?: A multilevel analysis of economy, welfare, and national identity in Europe - Jiménez,Antonia María Ruiz (2018)
Gone with the Crisis? A multilevel analysis of economy, welfare, and national identity in Europe. The development of the modern welfare state has been accompanied by an extension of economic, political, and social rights that created a sense of group belonging that then led to national solidarity. Our results show that the impact of the Great Recession cannot be rejected, and therefore that there is a rational-instrumental dimension to national identities that should not however be taken independently of cultural and political dimensions, and that must also be understood from a sociological point of view.